1525 The impact of sustained hot weather on risk of acute work-related injury in melbourne, australia. (24th April 2018) - McInnes, JA; MacFarlane, EM; Sim, MR; Smith, P
Abstract : Introduction: Increasing global temperatures will expose workers to hot days more often. The aim of this study was to quantify the impact of exposure to consecutive days of hot weather on the risk of work-related injury in Melbourne, Australia. Methods: A time-stratified case crossover study design was utilised to examine the association between 2 and 3 consecutive days and 2 and 3 consecutive nights of hot weather and risk of work-related injury, using definitions of hot weather ranging from the 60th to the 95th percentile of daily temperatures for the Melbourne metropolitan area, 2002–2012. Workers' compensation claim data were used to identify cases of work-related injury. Results: Overall, 2 and 3 consecutive days of hot weather was associated with an increased risk of injury for workers. This effect became apparent at 27.6°C, equivalent to the 70th percentile of maximum temperature distributions during the study period. Exposure to three days of hot weather and the highest temperatures was associated with the strongest effect, with a 15% increased risk of injury (OR: 1.15, 95% CI: 1.01 to 1.30) for workers exposed to temperatures ≥33.3°C (90th percentile) for 3 consecutive days, compared to those who were not. At a threshold of 35.5°C (95th percentile) there was no significant association between temperature and injury for either 2 or 3 consecutive days of heat. No consistent pattern was observed for hot nights, either with increasing levels of the temperature threshold or between two and three hot nights of exposure. Conclusions: Significant associations between consecutive days of hot weather and risk of work-related injury were apparent at relatively mild temperatures. These findings suggest warnings to minimise injury risk to workers from hot weather should be given and prevention protocols initiated when consecutive days of temperatures lower than extreme temperatures are forecast and before extreme temperatures are reached.